'Guided by the science': (De)politicising the UK government's response to the coronavirus crisis. (February 2022) - Kettell, Steven; Kerr, Peter
This article sets out to examine the politicising and depoliticising effects of the various stories that were deployed by the UK government in its response to the coronavirus crisis during its daily press briefings over a 2-month period between 16 March and 16 May 2020. In doing so, we identify four key narratives: (1) unprecedented government activism ; (2) working to plan ; (3) national security, wartime unity and sacrifice ; and (4) scientific guidance. Through a quantitative and qualitative study of the deployment of these narratives, we attempt to further recent theoretical insights on depoliticisation by noting that the COVID-19 crisis produced a particular type of crisis moment in which the government was forced to respond in 'real time' to a set of circumstances which were rapidly changing. As such, this made it much more difficult to control the various stories they wanted to tell and therefore find a coherent 'anchor' for their politicising and depoliticising strategies. This led to some deft discursive footwork as the government sought to pass the ball of responsibility between various groups of actors in order to rapidly and continually shift the balance between avoiding blame and taking credit.